Trace elements in striped dolphins (Stenella coeruleoalba) from the Eastern Mediterranean: A 10-years perspective. Issue 1 (15th August 2016) - Shoham-Frider, Efrat; Goffman, Oz; Harlavan, Yehudit; Kress, Nurit; Morick, Danny; Roditi-Elasar, Mia; Shefer, Edna; Kerem, Dan
Abstract: Concentrations of Hg, Se, Cd, Cu, Zn, Fe, Mn and As, in kidney, liver, muscle and blubber from 7 specimens of Stenella coeruleoalba, stranded along the Israeli Mediterranean coast (IMC) from 2006 to 2011 (2011-series) were determined and compared to previous data on S. coeruleoalba from the IMC (2001-series). No differences were observed in essential and toxic elements concentrations, between the two series, except for hepatic Mn which was higher in the latter. Hg/Se molar ratios in blubber, kidney and liver increased linearly with log Hg concentrations, while muscle was more heterogenic in this respect. Means (± SD) of hepatic Hg concentrations (134 ± 89 and 181 ± 200 mg kg − 1, from the 2011 and 2001 series, respectively) were similar to that found in 2007–2009 specimens from Spain, possibly reflecting the relatively high natural background levels of mercury in the Mediterranean Sea. Highlights: Overall, tissue levels of essential and toxic metals seem stable over time. Only Mn in liver showed significant increase from 2001 to 2011. As concentrations ranged from 0.19–2.86 ppm, blubber ranking second to the liver. Hg/Se ratio increased linearly with log Hg in blubber, kidney and liver. Hg concentrations are similar to specimens found in 2007–2009 from Spain.